KAJIAN LITERATUR PELUANG DAN TANTANGAN BISNIS KECIL DALAM PERSPEKTIF ENTREPRENEUSHIP - Achmad Fauzi; Ferida Rahmawati; Deva Nela Reditha; Jihan Nayla Atikah; Abdi Cahya Subekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the opportunities and challenges of small businesses from an entrepreneurship perspective through a literature review. The results show that small businesses have opportunities through digital technology, changing consumer behavior, government support, and innovation. However, they also face challenges such as limited capital, low innovation, digitalization barriers, limited human resources, and increasing competition. Therefore, entrepreneurial competence, digital utilization, and innovation are needed to support business sustainability and competitiveness